2013
DOI: 10.1163/15685411-00002683
|View full text |Cite
|
Sign up to set email alerts
|

Deladenus prorsus n. sp. (Nematoda: Neotylenchidae) in dunnage wood from Malaysia intercepted in Ningbo, China

Abstract: Deladenus prorsus n. sp., isolated from dunnage wood originating from Malaysia and intercepted in Ningbo port, P.R. China, is described and illustrated. The dunnage wood material appeared to have holes resembling the typical exit holes of wood-boring insects and have associated blue stain. The new species is characterised by the presence of both the mycophagous and infective forms {Deladenus consists of mycetophagous-only forms and those with known female dimorphism), the body length of 814 (670-1147) and 898 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Morphological study: The method used was as described previously (Yu et al, 2014). The nematodes were all fixed in TAF and mounted in dehydrated glycerin on slides for morphological studies.…”
Section: Methodsmentioning
confidence: 99%
“…Morphological study: The method used was as described previously (Yu et al, 2014). The nematodes were all fixed in TAF and mounted in dehydrated glycerin on slides for morphological studies.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, this feature overlaps between D. beddingi n. sp. and D. siricidicola, D. canii and D. valveus Yu, Popovic & Gu, 2014. The distance between the excretory pore and hemizonid in mycophagous females of D. nitobei is marginally shorter than in D. beddingi n. sp.…”
Section: Diagnosis and Relationshipsmentioning
confidence: 84%
“…Whilst several new species of dimorphic Deladenus nematodes have been described recently (Nasira et al, 2013;Yu et al, 2013Yu et al, , 2014Kanzaki et al, 2016), no new species thought to be a North American native has been reported or described from North America for several decades (Bedding & Akhurst, 1978;Yu et al, 2014). In general, species of Deladenus associated with the siricids found in western USA are poorly known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several species, including D. lonchites Massey, 1974;D. ruehmi Andrassy, 1958;and D. saccatus Andrassy, 1954, have been listed as species inquirendae (Chitambar, 1991;Siddiqi, 2000;Yu et al, 2014). Recently, six additional species have been described: D. cocophilus Nasira, Shahina and Firoza, 2013;D.…”
mentioning
confidence: 99%